Evolution of Cancer Care Delivery Research in the NCI Community Oncology Research Program - Geiger, Ann M (J Natl Cancer Inst, 2019)
Research seeking to improve patient engagement with decision-making, use of evidence-based guidelines, and coordination of multi-specialty care has made important contributions to the decades-long effort to improve cancer care. The National Cancer Institute expanded support for these efforts by including cancer care delivery research in the 2014 formation of the National Cancer Institute Community Oncology Research Program (NCORP). Cancer care delivery research is a multi-disciplinary effort to generate evidence-based practice change that improves clinical outcomes and patient well-being. NCORP scientists and community-based clinicians and organizations rapidly embraced the addition of this type of research into the network, resulting in a robust portfolio of observational studies and intervention studies within the first 5 years of funding. This commentary describes the initial considerations in conducting this type of research in a network previously focused on cancer prevention, control, and treatment studies; characterizes the protocols developed to date; and outlines future directions for cancer care delivery research in the second round of NCORP funding.